Assessment of Knowledge and Practice towards Hepatitis B among Medical and Health Science Students in Haramaya University, Ethiopia - Mesfin, Yonatan Moges; Kibret, Kelemu Tilahun (PLOS ONE, 2013)
Introduction Hepatitis B (HB) is a serious infection that affects liver and caused by hepatitis B virus (HBV). HB is a serious global public health problem and the health professionals are most at risk. It is contagious and easy to be transmitted from one infected individual to another by blood to blood contact, mother to child, unprotected sexual intercourse, sharing of eating utensils and other barber shop and beauty salon equipment. The aim of this study was to assess knowledge and practices about transmissions and prevention of hepatitis B among medical and health science students on clinical attachment in Haramaya University. Methods and Findings A cross sectional study was conducted among 322 health science and medical students who are starting clinical attachment (year II, III, IV, V and IV) from February 1–15, 2013. Self-administered structured questionnaire was used to collect information. Out of 322 distributed questionnaires, 322 were returned with a response rate of 100.0%. Majority of the students (91%) were in the age group 20–24 and 232 (72%) of the respondents were male. Majorities (95.3%) of students were not fully vaccinated against Hepatitis B and 48.4% of the students were not aware about the availability of post exposure prophylaxis for HB. Mean scores for knowledge and practice were 11.52±2.37 and 2.76±1.1 respectively. Significant and positive linear correlations between knowledge-practice (r = 0.173, p = 0.002) was observed. Study department was significantly associated with mean knowledge and practice of study respondents. Conclusion This study indicates that lack of awareness about Hepatitis B, its route of transmission and modes of prevention among the medical students entering into the profession. Similarly, 95.3% the students were not fully vaccinated against Hepatitis B, which makes them vulnerable to the disease.